Features of gallium spreading over surfaces of Ag - Au - Ga thin films - Andronov, V.M.; Dukarov, S.V.; Grebennik, I.P. (STC “Institute for Single Crystals”, 1997)
Linear spread of gallium over thin films of Ag-Au-Ga ternary alloys with continously varying concentrations along quasi-binary sections of the ternary diagram has been studied. The observed concentration dependence of the spread zone size is attributed to structural changes occurring in alloys and resulting in an unmonotonous dependence of the spread motive force on the alloy composition. . . . . . . . . . . . . . . . . . . . . . . . . Исследовано линейное растекание галлия по поверхности тонких пленок тройных сплавов серебро-золото-галлий с непрерывно изменяющейся концентрацией вдоль квазибинарных сечений тройной диаграммы. Обнаруженная немотонная зависимость размера зоны растекания от концентрации объясняется влиянием происходящих в сплавах структурных изменений, приводящих к немонотонной зависимости движущей силы растекания от состава сплава.
Keywords: Thin films; spreading; Wetting; Research Subject Categories::NATURAL SCIENCES::Physics::Condensed matter physics::Surfaces and interfaces